Quantitative assessment of knowledge gaps and research priorities for understanding and managing population irruptions of crown-of-thorns starfish (Acanthaster cf. solaris) on Australia’s Great Barrier Reef - Morgan S. Pratchett; Peter C. Doll; Christopher Cvitanovic; Shaun K. Wilson; Russell C. Babcock; Yves-Marie Bozec; Deborah Burn; Maria Byrne; Carolina Castro-Sanguino; Carla C. M. Chen; Scott A. Condie; Zara-Louise Cowan; et al. (Coral Reefs, 2026)
Despite extensive research on the western Pacific crown-of-thorns starfish (CoTS; Acanthaster cf. solaris ), especially from Australia’s Great Barrier Reef (GBR), there are persistent knowledge gaps that constrain understanding and management. Given renewed population irruptions of CoTS on the GBR, alongside escalating climate impacts and direct anthropogenic pressures, a quantitative assessment of knowledge gaps was undertaken to identify research priorities and guide future efforts. In this study, 27 experts independently scored 206 research questions across seven Themes and 39 topics, based on four different criteria ( Knowledge gap , Feasibility , Urgency , and Applicability ). These questions were ultimately rationalized into 170 distinct questions, with scores aggregated across merged questions. Management was the highest scoring Theme for Urgency , Applicability , and overall. All but six of the 20 top-ranked questions were from the Management Theme and mainly related to Culling and/ or Monitoring. Most questions (158 out of 170) also scored highly for Feasibility , suggesting that there are existing methods and technical capability available to advance the extensive and diverse range of research questions that were posed, if resources were made available. This quantitative assessment provides guidance on the prioritization of potential research that could improve management of CoTS populations to improve coral protection outcomes on the GBR. This study also suggests that there are limited constraints to undertaking necessary research to address many of the persistent knowledge gaps relating to CoTS.

Interspecific interaction, habitat, or neighborhood occupancy? Long-term dataset reveals factors influencing the barred owl invasion through time - Kaitlin R. McGee; Alan B. Franklin; Peter C. Carlson; Angela Rex; Paul Doherty, Jr. (Biological Conservation, 2026)

A Tale of Two Tails: Untangling the Phylogeography and Demographic History of Extant Species of Mulgara ( Dasycercus spp.) in the Australian Arid Zone - Aline Gibson Vega; Brenton von Takach; Linette Umbrello; Dympna Cullen; Mark Cowan; Helen Crisp; Chris Dickman; Tim Doherty; William La Marca; Jenny Molyneux; Colleen Sims; Peter B. S. Spencer; et al. (Journal of Biogeography, 2025)
Aim Australia's arid and semi‐arid zones cover about 70% of the continent, yet our understanding of the biogeography of these diverse and expansive landscapes remains limited. Mulgara ( Dasycercus spp.; Marsupialia: Dasyuridae), a widely distributed mammal taxon, offers an opportunity to explore patterns of the population structure across the region, previously hampered by taxonomic confusion surrounding extant species. Here, we aimed to (1) clarify the current distribution of extant Dasycercus lineages, (2) describe the population genomic structure of the widespread brush‐tailed mulgara, and (3) determine whether observed patterns of population genomic structure in brush‐tailed mulgara are consistent with biogeographic breaks. Location Arid and semi‐arid regions of Australia. Taxon Two species are extant; the brush‐tailed mulgara ( D. blythi ) and the crest‐tailed mulgara ( D. hillieri , previously D. cristicauda ). Methods We sampled individuals from contemporary and museum tissue collections, obtaining next‐generation sequencing data for 311 individuals, retaining 4360 single‐nucleotide polymorphisms (SNPs) for population genomic analysis. Results We found that the two extant species are clearly delineated, corresponding well to current understanding of their respective distributions. The population genomic substructure in the brush‐tailed mulgara (211 samples, 2740 SNPs) aligns primarily with major drainage divisions. Inference of historical population size change indicated that all populations have likely had stable population sizes for much of the past 1000 years, although post‐European colonisation declines in some populations cannot be ruled out. The Pilbara population was most differentiated from other populations and displayed a stronger pattern of isolation‐by‐distance. Nevertheless, observed heterozygosity was similar across each of the populations ( H o = 0.078–0.090). Conclusions Stable population dynamics linked to the ecology of the mulgara and their high dispersal potential likely explain consistent levels of genetic diversity across most populations, but the effects of geography, such as major drainage divisions, drive the apparent contemporary population structure. Additional targeted tissue collection in under‐sampled regions is recommended to better quantify genomic diversity, structure, and genetic health across the species' full range.

Ozone at Mace Head, Ireland from 1987 to 2021: Declining baselines, phase-out of European regional pollution, COVID-19 impacts - Richard G. Derwent; David D. Parrish; Alistair J. Manning; T. Gerard Spain; Peter G. Simmonds; Simon O'Doherty (Atmospheric Environment, 2024)

High-frequency, continuous hydrogen observations at Mace Head, Ireland from 1994 to 2022: Baselines, pollution events and ‘missing’ sources - Richard G. Derwent; Peter G. Simmonds; Simon O'Doherty; Alistair J. Manning; T. Gerard Spain (Atmospheric Environment, 2023)

Mapping cortical disease-burden at individual-level in frontotemporal dementia: implications for clinical care and pharmacological trials - Mary Clare McKenna; Marlene Tahedl; Jasmin Lope; Rangariroyashe H. Chipika; Stacey Li Hi Shing; Mark A. Doherty; Jennifer C. Hengeveld; Alice Vajda; Russell L. McLaughlin; Orla Hardiman; Siobhan Hutchinson; Peter Bede (Brain Imaging and Behavior, 2022)
Imaging studies of FTD typically present group-level statistics between large cohorts of genetically, molecularly or clinically stratified patients. Group-level statistics are indispensable to appraise unifying radiological traits and describe genotype-associated signatures in academic studies. However, in a clinical setting, the primary objective is the meaningful interpretation of imaging data from individual patients to assist diagnostic classification, inform prognosis, and enable the assessment of progressive changes compared to baseline scans. In an attempt to address the pragmatic demands of clinical imaging, a prospective computational neuroimaging study was undertaken in a cohort of patients across the spectrum of FTD phenotypes. Cortical changes were evaluated in a dual pipeline, using standard cortical thickness analyses and an individualised, z-score based approach to characterise subject-level disease burden. Phenotype-specific patterns of cortical atrophy were readily detected with both methodological approaches. Consistent with their clinical profiles, patients with bvFTD exhibited orbitofrontal, cingulate and dorsolateral prefrontal atrophy. Patients with ALS-FTD displayed precentral gyrus involvement, nfvPPA patients showed widespread cortical degeneration including insular and opercular regions and patients with svPPA exhibited relatively focal anterior temporal lobe atrophy. Cortical atrophy patterns were reliably detected in single individuals, and these maps were consistent with the clinical categorisation. Our preliminary data indicate that standard T1-weighted structural data from single patients may be utilised to generate maps of cortical atrophy. While the computational interpretation of single scans is challenging, it offers unrivalled insights compared to visual inspection. The quantitative evaluation of individual MRI data may aid diagnostic classification, clinical decision making, and assessing longitudinal changes.

Pharmacological inhibition of MERTK induces in vivo retinal degeneration: a multimodal imaging ocular safety assessment - Gregory Hamm; Gareth Maglennon; Beth Williamson; Ruth Macdonald; Ann Doherty; Stewart Jones; Jayne Harris; James Blades; Alexander R. Harmer; Peter Barton; Philip B. Rawlins; Paul Smith; et al. (Archives of Toxicology, 2022)
The receptor tyrosine kinase, MERTK, plays an essential role in homeostasis of the retina via efferocytosis of shed outer nuclear segments of photoreceptors. The Royal College of Surgeons rat model of retinal degeneration has been linked to loss-of-function of MERTK, and together with the MERTK knock-out mouse, phenocopy retinitis pigmentosa in humans with MERTK mutations. Given recent efforts and interest in MERTK as a potential immuno-oncology target, development of a strategy to assess ocular safety at an early pre-clinical stage is critical. We have applied a state-of-the-art, multi-modal imaging platform to assess the in vivo effects of pharmacological inhibition of MERTK in mice. This involved the application of mass spectrometry imaging (MSI) to characterize the ocular spatial distribution of our highly selective MERTK inhibitor; AZ14145845, together with histopathology and transmission electron microscopy to characterize pathological and ultra-structural change in response to MERTK inhibition. In addition, we assessed the utility of a human retinal in vitro cell model to identify perturbation of phagocytosis post MERTK inhibition. We identified high localized total compound concentrations in the retinal pigment epithelium (RPE) and retinal lesions following 28 days of treatment with AZ14145845. These lesions were present in 4 of 8 treated animals, and were characterized by a thinning of the outer nuclear layer, loss of photoreceptors (PR) and accumulation of photoreceptor outer segments at the interface of the RPE and PRs. Furthermore, the lesions were very similar to that shown in the RCS rat and MERTK knock-out mouse, suggesting a MERTK-induced mechanism of PR cell death. This was further supported by the observation of reduced phagocytosis in the human retinal cell model following treatment with AZ14145845. Our study provides a viable, translational strategy to investigate the pre-clinical toxicity of MERTK inhibitors but is equally transferrable to novel chemotypes.

Extra-motor cerebral changes and manifestations in primary lateral sclerosis - Eoin Finegan; Stacey Li Hi Shing; Rangariroyashe H. Chipika; Kai Ming Chang; Mary Clare McKenna; Mark A. Doherty; Jennifer C. Hengeveld; Alice Vajda; Niall Pender; Colette Donaghy; Siobhan Hutchinson; Russell L. McLaughlin; et al. (Brain Imaging and Behavior, 2021)

Chronic kidney disease of unknown origin is associated with environmental urbanisation in Belfast, UK - Jennifer M. McKinley; Ute Mueller; Peter M. Atkinson; Ulrich Ofterdinger; Siobhan F. Cox; Rory Doherty; Damian Fogarty; J. J. Egozcue; V. Pawlowsky-Glahn (Environmental Geochemistry and Health, 2021)
Chronic kidney disease (CKD), a collective term for many causes of progressive renal failure, is increasing worldwide due to ageing, obesity and diabetes. However, these factors cannot explain the many environmental clusters of renal disease that are known to occur globally. This study uses data from the UK Renal Registry (UKRR) including CKD of uncertain aetiology (CKDu) to investigate environmental factors in Belfast, UK. Urbanisation has been reported to have an increasing impact on soils. Using an urban soil geochemistry database of elemental concentrations of potentially toxic elements (PTEs), we investigated the association of the standardised incidence rates (SIRs) of both CKD and CKD of uncertain aetiology (CKDu) with environmental factors (PTEs), controlling for social deprivation. A compositional data analysis approach was used through balances (a special class of log contrasts) to identify elemental balances associated with CKDu. A statistically significant relationship was observed between CKD with the social deprivation measures of employment, income and education (significance levels of 0.001, 0.01 and 0.001, respectively), which have been used as a proxy for socio-economic factors such as smoking. Using three alternative regression methods (linear, generalised linear and Tweedie models), the elemental balances of Cr/Ni and As/Mo were found to produce the largest correlation with CKDu. Geogenic and atmospheric pollution deposition, traffic and brake wear emissions have been cited as sources for these PTEs which have been linked to kidney damage. This research, thus, sheds light on the increasing global burden of CKD and, in particular, the environmental and anthropogenic factors that may be linked to CKDu, particularly environmental PTEs linked to urbanisation.

Spatial Ecology of Sub-Adult Green Turtles in Coastal Waters of the Turks and Caicos Islands: Implications for Conservation Management - Philip D. Doherty; Annette Cameron Broderick; Brendan John Godley; K. A. Hart; Q. Phillips; A. Sanghera; Thomas B. Stringell; J. T. Walker; Peter Bradley Richardson (Frontiers in Marine Science, 2020)

Connectivity-based characterisation of subcortical grey matter pathology in frontotemporal dementia and ALS: a multimodal neuroimaging study - Peter Bede; Taha Omer; Eoin Finegan; Rangariroyashe H. Chipika; Parameswaran M. Iyer; Mark A. Doherty; Alice Vajda; Niall Pender; Russell L. McLaughlin; Siobhan Hutchinson; Orla Hardiman (Brain Imaging and Behavior, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

History of hypertension, heart disease, and diabetes and ovarian cancer patient survival: evidence from the ovarian cancer association consortium - Albina N. Minlikeeva; Jo L. Freudenheim; Rikki A. Cannioto; J. Brian Szender; Kevin H. Eng; Francesmary Modugno; Roberta B. Ness; Michael J. LaMonte; Grace Friel; Brahm H. Segal; Kunle Odunsi; Paul Mayor; et al. (Cancer Causes & Control, 2017)

A synoptic climatology of strong along‐channel winds on the Coast of British Columbia, Canada - Talaat Bakri; Peter Jackson; Ford Doherty (International Journal of Climatology, 2017)
A synoptic climatology using mean sea level pressure and 500‐ hPa geopotential height composites is conducted for strong along‐channel winds that occur through five of the channels dissecting British Columbia's coast. Seasonal (winter, summer) and directional (inflow, air moving from the coast inland; outflow, air moving from inland towards the coast) partitioning of the winds, results in four distinct along‐channel winds that occur: summertime inflow, summertime outflow, wintertime inflow and wintertime outflow. Composite analyses using reanalysis data and in situ observations are used to examine each wind type at all locations. Wintertime composites produce patterns that are distinct from the overall winter climatology, in which outflows occur when an arctic surface high‐pressure area on the inland side of the coastal mountains is accompanied by the presence of an area of low surface pressure in the northeastern Pacific. Inflow composites in the winter indicate low‐pressure areas associated with mid‐latitude cyclones over the Gulf of Alaska. Summertime composites are similar to the overall summer climatology; therefore, other approaches are applied to explain these winds. We analyse 104 summertime inflow events at three locations using surface analysis charts for 13 summer seasons. The analysis reveals the importance of fronts at the time of inflows, with fronts associated with almost half of the events. Non‐hierarchical clustering analysis is applied for the summertime inflow events. The clustering analysis gives a better explanation of the summertime inflows than the composites. This is achieved by grouping events into different clusters, allowing for better illustration of the variance between the clusters.

Large‐scale, multidirectional larval connectivity among coral reef fish populations in the Great Barrier Reef Marine Park - David H. Williamson; Hugo B. Harrison; Glenn R. Almany; Michael L. Berumen; Michael Bode; Mary C. Bonin; Severine Choukroun; Peter J. Doherty; Ashley J. Frisch; Pablo Saenz‐Agudelo; Geoffrey P. Jones (Molecular Ecology, 2016)
Larval dispersal is the key process by which populations of most marine fishes and invertebrates are connected and replenished. Advances in larval tagging and genetics have enhanced our capacity to track larval dispersal, assess scales of population connectivity, and quantify larval exchange among no‐take marine reserves and fished areas. Recent studies have found that reserves can be a significant source of recruits for populations up to 40 km away, but the scale and direction of larval connectivity across larger seascapes remain unknown. Here, we apply genetic parentage analysis to investigate larval dispersal patterns for two exploited coral reef groupers ( Plectropomus maculatus and Plectropomus leopardus ) within and among three clusters of reefs separated by 60–220 km within the Great Barrier Reef Marine Park, Australia. A total of 69 juvenile P. maculatus and 17 juvenile P. leopardus (representing 6% and 9% of the total juveniles sampled, respectively) were genetically assigned to parent individuals on reefs within the study area. We identified both short‐distance larval dispersal within regions (200 m to 50 km) and long‐distance, multidirectional dispersal of up to ~250 km among regions. Dispersal strength declined significantly with distance, with best‐fit dispersal kernels estimating median dispersal distances of ~110 km for P. maculatus and ~190 km for P. leopardus . Larval exchange among reefs demonstrates that established reserves form a highly connected network and contribute larvae for the replenishment of fished reefs at multiple spatial scales. Our findings highlight the potential for long‐distance dispersal in an important group of reef fishes, and provide further evidence that effectively protected reserves can yield recruitment and sustainability benefits for exploited fish populations.

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Coupled Chemical Shrinkage and Consolidation: Some Benchmark Solutions - David Muir Wood; James Peter Doherty (Transport in Porous Media, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Genome-wide association study of endometrial cancer in E2C2 - Immaculata De Vivo; Jennifer Prescott; Veronica Wendy Setiawan; Sara H. Olson; Nicolas Wentzensen; John Attia; Amanda Black; Louise Brinton; Chu Chen; Constance Chen; Linda S. Cook; Marta Crous-Bou; et al. (Human Genetics, 2014)

Workshop on the ecosystem and fisheries of the Coral Sea: an Australian perspective on research and management - Jock W. Young; A. David McKinnon; Daniela Ceccarelli; Richard Brinkman; Rodrigo H. Bustamante; Mike Cappo; Cathy Dichmont; Peter Doherty; Miles Furnas; Daniel Gledhill; Shane Griffiths; Trevor Hutton; et al. (Reviews in Fish Biology and Fisheries, 2012)

Delineation of the molecular mechanism for disulfide stress-induced aluminium toxicity - Ming J. Wu; Patricia A. Murphy; Patrick J. O’Doherty; Stephen Mieruszynski; Mark Jones; Cindy Kersaitis; Peter J. Rogers; Trevor D. Bailey; Vincent J. Higgins (BioMetals, 2012)

Respiratory epithelial cells in innate immunity to influenza virus infection - Catherine J. Sanders; Peter C. Doherty; Paul G. Thomas (Cell and Tissue Research, 2011)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Geochemistry of Tertiary tholeiites and picrites from Qeqertarssuaq (Disko Island) and Nuussuaq, West Greenland with implications for the mineral potential of comagmatic intrusions - Peter C. Lightfoot; Christopher J. Hawkesworth; Kevin Olshefsky; Tony Green; Will Doherty; Reid R. Keays (Contributions to Mineralogy and Petrology, 1997)

Directional Swimming of Fish Larvae Determines Connectivity of Fish Populations on the Great Barrier Reef - Eric Wolanski; Peter Doherty; John Carleton (The Science of Nature, 1997)